PEMBERIAN TERAPI MUSIK KLASIK UNTUK MENURUNKAN INTENSITAS NYERI PADA PASIEN POST SECTIO CAESAREA (SC) DI RUANG DAHLIA RST BHAKTI WIRA TAMTAMA SEMARANG - aprilia, ni'amatun; Wulaningsih, Indah (NHM PRESS, 2024)
Background: Sectio Caesarea (SC) is a way to deliver a fetus by making an incision in the uterine wall through the front wall of the abdomen. Mothers who undergo SC surgery will feel pain in the area of ​​the incision wound and will gradually recover over 6 weeks, while for recovery the problem of numbness, soreness or itching around the wound can last up to 6 months. One distraction technique for pain relief is classical music therapy. Classical music therapy can provide calm with soft strains that are in harmony with the pulse, thereby causing a distraction effect on thoughts about pain Objective: To describe the application of is classical music therapy to treat pain in post sectio caesarea patients in the Dahlia Room RST Bhakti Wira Tamtama Semarang. Method: Using a descriptive method by describing nursing care for post sectio caesarea patients in the Dahlia Room RST Bhakti Wira Tamtama Semarang, using pre-test and post-test. The research was conducted on 21-23 November 202. Results: After carrying out the classical music therapy intervention to treat pain, the result showed a reduction in pain in post sectio caesarea patients. Conclusion: Clients are able to overcome pain by providing classical music therapy. Pain is reduced from severe to mild, optimized with pharmacological pain management using analgesics as indicated. Suggestion: It is hoped that patients and families can carry out routine treatment and therapy programs.